2021
DOI: 10.3389/fonc.2021.695627
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Treatment in Pancreatic Cancer: Shaping the Future of the Curative Setting

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is a lethal disease even in the early stages, despite progresses in surgical and pharmacological treatment in recent years. High potential for metastases is the main cause of therapeutic failure in localized disease, highlighting the current limited knowledge of underlying pathological processes. However, nowadays research is focusing on the search for personalized approaches also in the adjuvant setting for PDAC, by implementing the use of biomarkers and investigating n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 123 publications
1
5
0
Order By: Relevance
“…AHT, type 2 DM, abdominal pain, CA 19.9 > 500 U/mL, T > 2, N+, M1, LVI, Clavien-Dindo > IIIa, stage > II, R ≥ 1, tumor size > 2 cm, and recurrence were found as prognostic factors for OS in our analysis, which is in agreement with previous studies. Adjuvant treatment was associated with a reduction in the risk of death, prolonging OS, which was also previously known [39]. Multivariate analysis showed that AHT, DM, and Clavien-Dindo > IIIa are independent risk factors for mortality in these patients.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…AHT, type 2 DM, abdominal pain, CA 19.9 > 500 U/mL, T > 2, N+, M1, LVI, Clavien-Dindo > IIIa, stage > II, R ≥ 1, tumor size > 2 cm, and recurrence were found as prognostic factors for OS in our analysis, which is in agreement with previous studies. Adjuvant treatment was associated with a reduction in the risk of death, prolonging OS, which was also previously known [39]. Multivariate analysis showed that AHT, DM, and Clavien-Dindo > IIIa are independent risk factors for mortality in these patients.…”
Section: Discussionsupporting
confidence: 69%
“…Second, only 58.1% of patients received adjuvant treatment, so the tumor recurrence rate and DFS after surgery could be affected, although its administration complied with the protocols of the institution. However, up to 30% of PDAC patients do not receive adjuvant therapy because of the development of comorbidities, worsening of performance status, postoperative complications and/or early recurrence [39] and for those receiving the treatment, delays and dose modifications are common [53]. Third, evaluating only a small area of the tumor tissue may not adequately reflect its entire architecture, which could make this method insufficient to estimate prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…In most cases they were referred to our specialized center for surgery, and were discharged and referred to peripheral centers for follow-up and adjuvant treatments. Nevertheless, even though several trials reported that adjuvant chemotherapy may prolong the disease-free survival and metastasis-free survival in resected PDAC patients [ 2 , 26 ], things are different in the “real world”; up to 30% of patients do not receive all the planned cycles of adjuvant chemotherapy, within a short interval from surgery, because of comorbidities, the worsening of performance status, and post-operative complications [ 27 ]. Therefore, the real benefit of adjuvant therapy is not clearly established.…”
Section: Discussionmentioning
confidence: 99%
“…The PRODIGE24 trial reported the longest survival outcome in pancreatic cancer patients who received adjuvant mFOLFIRINOX (oxaliplatin, irinotecan, leucovorin, and fluorouracil) regimen following surgery, but with a higher incidence of AEs, particularly neutropenia and diarrhea [8] . Therefore, mFOLFIRINOX is regarded as the best adjuvant regimen in very fit and well-selected patients [18] . Notably, some meta-analyses argued that S-1 adjuvant chemotherapy provides DFS and OS similar to or better than mFOLFIRINOX, and S-1 is better for overall and hematologic grade 3 or 4 toxicities [ 11 , 19 ].…”
Section: Discussionmentioning
confidence: 99%